(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
his article examines ai-based audit systems: prospects for detecting financial fraud and reducing the shadow economy through an integrated finance, accounting, and institutional governance perspective. It combines recent international standards discussions, Uzbekistan’s 2021-2025 digitalization trajectory, and analytical mechanisms linking data quality with transparency outcomes. The study argues that digital architecture produces durable anti-shadow effects only when artificial intelligence, professional judgment, and compliance design are aligned within accountable institutions.